EVALUATING THE MERGER PROCESS OF PUBLIC COMPANIES IN IRAQ ACCORDING TO INTERNATIONAL ACCOUNTING STANDARDS-AN APPLIED STUDY OF THE GENERAL COMPANY FOR TEXTILE AND LEATHER INDUSTRIES - Hazem Ali Muttair; Suhair Kadhim Fadhil (Scholar Express Journals, 2025)
As a result of the continuous development of economic life and the emergence of diverse commercial companies, economic concentration has become a contemporary feature. Mergers have become one of the most important means of achieving this concentration, with the goal of achieving greater profits and broader competition. The study aimed, through studying the reality of evaluating the process of merging public companies in Iraq in the Iraqi environment, to identify the most important difficulties that accompanied the process of merging public companies, and to clarify the principles that must be followed when merging, which are consistent with the legal legislation of the local environment, with a statement of the impact of the merger when preparing financial statements in accordance with international accounting standards. The study was conducted on a sample of public companies that have a significant impact on the Iraqi economy and apply the unified accounting system. These companies exist in an economic environment characterized by constant dynamics and fluctuations, and purchasing power therefore changes with these conditions. The study concluded that adapting the International Financial Reporting Standard (IFRS 3) to assess the merger process of public companies in Iraq helps provide results closer to accuracy and reality when preparing financial statements. Mergers of companies are considered one of the main financial solutions for struggling companies.
Keywords: Merger; acquisition; public companies